Converting pork into porcelain: cultural institutions and downtown development - Strom, Elizabeth (2002)
The importance of cultural institutions to contemporary revitalization efforts in U.S. cities is attributed to several factors. First, the transformation of the urban political economy has made cities more dependent on their consumption economies. Second, urban cultural institutions have a strong interest in improving their surroundings, especially now that they have become more dependent on revenue-generating activities and on funding sources interested in attracting broad audiences. Finally, cultural hierarchies have become less rigid, allowing cultural institutions to draw on serious and popular art forms. - Reproduced.
Keywords: Cultural organizations